Variable saline resuscitation in a murine model of combined traumatic brain injury and haemorrhage. (6th December 2018) - Jung, Andrew; Johnson, Mark; Veile, Rosalie; Friend, Lou Ann; Stevens-Topie, Sabre; Elterman, Joel; Pritts, Timothy; Makley, Amy; Goodman, Michael
ABSTRACT: Background : Resuscitation strategies for combined traumatic brain injury (TBI) with haemorrhage in austere environments are not fully established. Our aim was to establish the effects of various saline concentrations in a murine model of combined TBI and haemorrhage, and identify an effective resuscitative strategy for the far-forward environment. Methods : Male C57BL/6 mice underwent closed head injury and subjected to controlled haemorrhage to a systolic blood pressure of 25 mmHg via femoral artery cannulation for 60 min. Mice were resuscitated with a fixed volume bolus or variable volumes of fluid to achieve a systolic blood pressure goal of 80 mmHg with 0.9% saline, 3% saline, 0.1-mL bolus of 23.4% saline, or a 0.1-mL bolus of 23.4% saline followed by 0.9% saline (23.4+). Results : 23.4% saline and 23.4+ resulted in higher mortality at 6 h compared to 0.9% saline. Use of 3% saline required less volume to achieve targeted resuscitation, did not affect survival, and did not exacerbate post-traumatic inflammation. While 23.4+ resuscitation utilized lower volume, it resulted in hypernatremia, azotemia, and elevated systemic pro-inflammatory cytokines. All groups except 3% saline demonstrated progression of neuron damage, with cerebral oedema highest with 0.9% saline. Conclusions : 3% saline demonstrated favourable balance of survival, blood pressure restoration, minimization of inflammation, and prevention of ongoing neurologic injury without contributing to significant physiologic derangements. 23.4% saline administration may not be appropriate in the setting of concomitant hypotension.